Going green with bionanocomposites - Ahmad @ Ayob, Mansor (Universiti Putra Malaysia Press, 2016)
Polymers play a great part in our daily lives and without them around, this world would be very, very different, if not impossible to live in. Nevertheless, most people do not even know what polymers are, or just how prevalent they are around us. Many a time, the term polymer is used to refer to plastics, but it actually comprises a larger class of natural and synthetic materials with a wide range of properties and applications. A variety of polymers exist in nature, such as cotton, cellulose, shellac, amber, silk, ribonucleic acid (RNA) and deoxyribonucleic acid (DNA). Synthetic polymers include polyethylene, polypropylene, polystyrene, synthetic rubber, neoprene, nylon, polyvinyl chloride (PVC), Teflon, silicone, polyacrylonitrile, and many others. Monomers are essentially the building blocks of the molecules that make up everything, living and non-living, naturally occurring and man-made. A polymer may contain thousands of monomers, or just a few. Each monomer affects how that polymer looks, tastes, smells and behaves.